RISBILOR (Sweet Potato and Moringa Risol) in Increasing the Quantity of Breast Milk Production in Breastfeeding Mothers - Nurakilah, Heni; Sulastri, Meti; Sopiah Suryani, Iis; Assidiqy, Birry; Ulfah Jamil, Maria (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Optimal breast milk (BM) production is a crucial factor in the success of exclusive breastfeeding, yet many breastfeeding mothers still experience challenges related to low milk quantity. One of the factors influencing breast milk production is the adequacy of maternal nutrition during lactation. The utilization of local nutrient-rich foods with galactagogue properties offers a potential alternative to enhance breast milk production. This study aimed to examine the effect of sweet potato leaves and moringa leaves, processed into RISBILOR (Sweet Potato and Moringa Risoles), on increasing BM quantity and improving exclusive breastfeeding coverage in the working area of Kersanagara Community Health Center, Tasikmalaya City. A quasi-experimental design with a pretest–posttest control group was used. The study involved 40 breastfeeding mothers with infants aged 0–6 months, who received the intervention for 14 consecutive days. The results showed a significant difference in BM quantity between the intervention and control groups after RISBILOR administration, with a Wilcoxon test p-value of 0,032 (p-value <0,05). In conclusion, RISBILOR significantly increased breast milk production in mothers of infants aged 0–6 months, indicating that it can be used as a safe and beneficial local food-based functional food to support breast milk production and the success of exclusive breastfeeding programs.